A study of Mathematical Problem-solving Ability Using Problem-Based Learning of Grade 7th students - Soikudrua, Bunjamaphon; Nontapa, Ramnaree (Journal of Education Rajabhat Maha Sarakham University, 2024)
This research purposese were to study the mathematical problem-solving ability of Grade 7th students on the topics of decimals and fractions by using problem-based learning compared to the 70% criterion. The sample consists of 40 Grade 7th students from Sarakhampittayakhom School, Mueang Maha Sarakham District, Maha Sarakham Province, during the first semester of the 2023 academic year. The research tools were: 1) 10 problem-based learning lesson plans and 2) a subjective test on mathematical problem-solving with 25 questions on decimals and fractions. The statistics used percentage, mean, and standard deviation. The research result revealed that the students' mathematical problem-solving ability in the first test earned mean score of 3.95. The most of 24 of 40 students, demonstrated a level 4 problem-solving ability, accounting for 60.00%. Following this, 9 students (22.50%) had a level 3 problem-solving ability, and 7 students (17.50%) achieved level 5. There was not any student fell into the level 0-2 categories, representing 0.00%. In the second test, their mean score increased to 4.03. The majority of students, 23 out of 40, showed a level 4 problem-solving ability, representing 57.50%. 9 students (22.50%) had a level 5 problem-solving ability, while 8 students (20.00%) were at level 3. Again, no students were at levels 0-2, accounting for 0.00%. In the third test, their mean score slightly increased to 4.05. The 24 of 40 students, maintained a level 4 problem-solving ability, accounting for 60.00%. 9 students (22.50%) reached level 5, and 7 students (17.50%) were at level 3. There was not any student at levels 0-2, representing 0.00%. Among the high-achieving students, 10 students (71.43%) achieved level 5 problem-solving ability.